(untitled) (Pesquisa Odontológica Brasileira, 2000)
One hundred and forty-four Brazilian AIDS patients presenting with Kaposis sarcoma (KS) were evaluated with respect to the frequency of oral neoplasms and their clinical features. The majority of the patients were young male adults (age range: 21-40 years old), from which 11.1 % presented with oral KS (OKS) exclusively. Oral and skin lesions were associated in 25% of the cases, while only four patients showed association between oral and visceral KS; 49.3% of the cases were exclusively dermatological. The hard palate was the main site affected, followed by the oropharynx. The localization of KS was found to be similarly frequent in the tongue, gingiva and other sites of the oral mucosa. Candidosis was the prevailing fungal disease; in 20% of the cases it was restricted to the oral mucosa and in 80% it was systemic. No high frequency of paracoccidioidomicosis and cryptococcosis was detected. The prevailing bacterial disease was Tuberculosis and there was only one case of syphilis. Among the viral diseases, the most frequently detected was herpes simplex, followed by molusco contagiosum, condiloma acuminatum and cytomegaloviroses at lower frequencies. Pneumonia caused by Pneumocystes carinii and toxoplasmosis were also identified. The authors emphasise the importance of oral examination in HIV-infected patients bearing in mind several aspects related especially to KS, and stress the need for an interdisciplinary team in the management of these patients, in order to provide better quality of life as well as rapid diagnosis and treatment.